2011
DOI: 10.1123/jsep.33.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Efficacy and Exploratory Structural Equation Modeling: A Substantive-Methodological Synergy

Abstract: The purpose of this article was to provide a substantive-methodological synergy of potential importance to future research in sport and exercise psychology. The substantive focus was to improve the measurement of coaching efficacy by developing a revised version of the coaching efficacy scale (CES) for head coaches (N = 557) of youth sport teams (CES II-YST). The methodological focus was exploratory structural equation modeling (ESEM), a methodology that integrates the advantages of exploratory factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
(73 reference statements)
3
23
0
3
Order By: Relevance
“…More precisely, these studies had no clear hypothesis regarding which indicators should load on the factors and employ ESEM to explore the data to come up with a solution. Finally, only one study (Myers, Chase, Pierce, & Martin, 2011) starts by specifying a clear expected a priori structure (i.e. ESEM as a replacement for CFA), but also supplement this approach by an exploratory data-driven process where solutions including different numbers of factors are contrasted in a classical EFA manner.…”
Section: Why Use Esem Over the Cfa-independent Cluster Model?mentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, these studies had no clear hypothesis regarding which indicators should load on the factors and employ ESEM to explore the data to come up with a solution. Finally, only one study (Myers, Chase, Pierce, & Martin, 2011) starts by specifying a clear expected a priori structure (i.e. ESEM as a replacement for CFA), but also supplement this approach by an exploratory data-driven process where solutions including different numbers of factors are contrasted in a classical EFA manner.…”
Section: Why Use Esem Over the Cfa-independent Cluster Model?mentioning
confidence: 99%
“…The sequential strategy that was followed in the present study and the details of model specifications were devised from the work of Meredith (1993) and Millsap (2011) on the invariance of CFA models, Millsap and Tein (2004) and on the invariance of CFA models based on ordered-categorical items, and of Marsh et al (2009) andMyers, Chase, Pierce, and on the adaptation of these tests to ESEM. For a formal mathematical presentation of these specifications, the interested reader is referred to Millsap (2011).…”
Section: Appendix Cmentioning
confidence: 99%
“…The picture with regard to model fit is somewhat more mixed. In five studies, both the CFA and ESEM solutions display good fit (Marsh, Liem, et al, 2011a;Morin & Maiano, 2011;Myers et al, 2011;Sánchez-Carracedo et al, 2012). In one study (Studerus et al, 2010) both CFA and ESEM showed poor fit.…”
Section: Introductionmentioning
confidence: 99%
“…En skala om treneres mestringstropsykometriske kvaliteter I de senere årene har skalaen for måling av mestringstro for trenere gjennomgått utstrakt psykometrisk testing (for en oversikt, se Myers, Chase, Pierce, & Martin, 2011). Tidlige tester av skalaens modelltilpasning viste i flere tilfeller uakseptable verdier; eksempelvis .87-.89 for CFI og .08-.09 for RMSEA.…”
Section: Introduksjonunclassified
“…Spesielt så man dette i studier blant idrettsutøvere innen amerikansk idrett på videregående/gymnasnivå (Feltz et al, 1999). Samtidig viser senere valideringsforsøk på tilsvarende utvalg noe bedre resultater (for en oversikt, se Myers, Feltz, & Wolfe, 2008;Myers et al, 2011).…”
Section: Introduksjonunclassified